Diversity and blooming season of food sources plant of Apis cerana (Hymenoptera: Apidae) in polyculture plantation in West Sumatra, Indonesia - JASMI JASMI (Society for Indonesian Biodiversity, 2017)
Abstract. Jasmi. 2017. Diversity and blooming season of food sources plant of Apis cerana (Hymenoptera: Apidae) in polyculture plantation in West Sumatra, Indonesia. Biodiversitas 18: 34-40. The existence of honeybees in a habitat was highly affected by the presence of food source plant. Therefore, the research was conducted to examine the diversity and the blooming season of food source plant of Apis cerana Fabr. in polyculture plantation in West Sumatra from March 2011 to March 2012. Samples were collected with a plot method of 100 m x 100 m on altitudes of <100 m and >1.000 m asl. The results showed that 94 species (34 families) of food source plants for A. cerana were found. The most found species were Asteraceae (12 species) and Leguminoceae family (10 species). On the plateau, food source plants were 21 species, while on lowland there were 18 species and on both altitudes, there were 55 species (similarity index 75.34%). The number of cultivated plants was 46 species and the number of wild plants was 48 species. The cultivated plants in lowland were 34 species and 33 species in the plateau (similarity index 59.70%). Plants that bloom all year round were 59 species, plants that bloom depending on growing season were 15 species and annual plants that bloom annually were 20 species. The largest number of flowering plants was found in August with 88 species out of 94 species found.Keywords: Apis cerana, blooming season, diversity, food source plant, polyculture plantation